2014
DOI: 10.1016/j.chemphyslip.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol stabilizes fluid phosphoinositide domains

Abstract: Local accumulation of phosphoinositides (PIPs) is an important factor for a broad range of cellular events including membrane trafficking and cell signaling. The negatively charged phosphoinositide headgroups can interact with cations or cationic proteins and this electrostatic interaction has been identified as the main phosphoinositide clustering mechanism. However, an increasing number of reports show that phosphoinositide-mediated signaling events are at least in some cases cholesterol dependent, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 47 publications
(75 reference statements)
5
63
0
Order By: Relevance
“…One important feature could be a prearrangement of lipid species into domains that in turn could affect AnxA2 binding. Such preformed domains, in particular a cholesterol-dependent clustering of PI(4,5)P 2 , have indeed been observed in model membranes containing 20 mol % porcine brain PI(4,5)P 2 (75)(76)(77). However, our bilayer composition containing 3% PI(4,5)P 2 with two unsaturated acyl chains showed no tendency of forming micrometer-sized lipid domains, at least when analyzed in GUVs using labeled PI(4,5)P 2 (13).…”
Section: Discussionmentioning
confidence: 82%
“…One important feature could be a prearrangement of lipid species into domains that in turn could affect AnxA2 binding. Such preformed domains, in particular a cholesterol-dependent clustering of PI(4,5)P 2 , have indeed been observed in model membranes containing 20 mol % porcine brain PI(4,5)P 2 (75)(76)(77). However, our bilayer composition containing 3% PI(4,5)P 2 with two unsaturated acyl chains showed no tendency of forming micrometer-sized lipid domains, at least when analyzed in GUVs using labeled PI(4,5)P 2 (13).…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, recent MD simulations suggested that MA may induce lateral segregation of PI(4,5)P 2 into domains which may by itself promote efficient MA binding, for example through locally enhanced electrostatic interactions (78). There is also experimental evidence that cholesterol helps stabilize PI(4,5)P 2 in lipid clusters (79), which rationalizes that cholesterol and PI(4,5)P 2 synergistically attract MA to the membrane, as shown in Fig. 4 and 5.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoinositides are also commercially available with di-oleoyl (DOPIPs) or di-palmitoyl acyl (di-C 16 PIPs) chains. DOPIPs will form fluid phases, however, the phase behavior in the presence of other membrane components like cholesterol deviates slightly from what is observed for SAPIPs [17]. DPPIPs form ordered (gel) phases at room temperature [18], resulting in a reduced mobility and lateral spacing of di-C 16 PIPs in comparison to SAPIPs and even though PTEN penetrates the bilayer only to a limited extent [19, 20], bilayer model systems involving saturated chain phosphoinositides are less suitable to study PTEN membrane association.…”
Section: Biomembrane Mimics For the Characterization Of Membrane-amentioning
confidence: 99%